PKM SEKOLAH BERBASIS KESEHATAN DAN LINGKUNGAN DI SD NEGERI 5 SINGAKERTA UBUD GIANYAR BALI - Lestari, Ni Kadek Dwipayani; Adisanjaya, Nyoman Ngurah; Rosiana, I Wayan (JURNAL WIDYA LAKSANA, 2022)
The health and environment program is a program that focuses on the school's commitment to preventing disease during a pandemic and maintaining cleanliness and preserving the environment. This program is in line with the government's goals to jointly protect the environment amid the Covid-19 pandemic. The choice of primary school is not only because basic education is accepted here, it is also possible to instill environmental awareness as early as possible in school children to care more about the surrounding environment and instill the importance of health protocols. Singakerta 5 State Elementary School is located on Jalan Raya Br. Tunon No. 4 Singakerta Ubud Gianyar Bali, where this school has been accredited A. The number of male students is 52 students and 54 girls and has 9 teachers. This school is led by I Wayan Metro as the Principal of the School. From the results of field observations, 3 main problems were obtained, namely 1) Environmental Health in particular how to provide knowledge about personal health for elementary school children, prevention of viruses and bacteria and provision of adequate health facilities, 2) Problems in the field of Information Technology (Computer), in accordance with the circular of the Governor of Bali to hold E-Learning in their respective homes during school holidays, so that knowledge and training are needed for teachers and students about the system, 3) Problems in the field of Biology, according to the objectives of environment-based schools, are appropriate training and assistance, especially in the field of Biology. Activities in the field of Environmental Health include the provision of health protocol facilities, assistance in the management of health protocols, procurement of garbage bins, assistance for sorting waste and composting. And in the field of information technology, namely assistance in the use of E-learning such as Google meet and Google classroom. Meanwhile, in the field of Biology, training and assistance in the maintenance and cultivation of plant nurseries will be conducted. Each activity is measured the level of progress of its success by conducting tests both before and after the activity, monitoring and evaluating scheduled.